Kesiapan Pelaporan Keberlanjutan Pemerintah Daerah: Kepatuhan Standar Gri di Bantul dan Sleman - Ruscitasari, Zulfatun; Marzuqoh, Mamluatul; Mutia, Galuh Ratna (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the readiness of sustainability reporting in the regional governments of Bantul and Sleman by measuring their level of compliance with the Global Reporting Initiative (GRI) standards, particularly the GRI 200 (economic) and GRI 300 (environmental) standards. The assessment is conducted by measuring the percentage of alignment between the information presented by the regional governments on their respective websites and the information required by the GRI indicator standards. Research methodology: This study uses secondary data in the form of public information available on the websites of the Bantul and Sleman Regional Governments. Results: The research results show significant efforts in revealing economic and environmental performance. However, there are still shortcomings in the completeness and clarity of information. Some GRI indicators, such as GRI 202, 204, 205, 206, 301, 304, and 305, have not been fully disclosed. Both regional governments have disclosed a lot of data on waste management (GRI 303), but still need improvements in systems, human resources and infrastructure to increase transparency and accountability Limitations: This study only uses content analysis from official local government reports, so there are data limitations. Future research could add interviews or surveys with stakeholders to understand the challenges and opportunities in implementing sustainability report. Contribution: This research helps understand sustainability reporting practices at the local government level, provides recommendations for improvement, and supports the achievement of sustainable development goals (SDGs).